2019
DOI: 10.2495/eq-v4-n3-198-208
|View full text |Cite
|
Sign up to set email alerts
|

Unconventional small-scale biogas production with reduced local impact

Abstract: One of the problems of food waste management is the acceptability of the treatment plants at local level because of the risk of odours. Anaerobic digestion as first step before composting has contributed to solve this problem, but, in the sector, it remains an opposition to large plants. That affects also food waste anaerobic digestion: people's perception is that the stream coming at the gate of the plant is not theirs. The present paper shows an alternative to the conventional approach. The aim is to reduce … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 19 publications
0
6
0
1
Order By: Relevance
“…In the perspective of reducing the carbon emissions, improving resource efficiency, minimizing waste production and potential damages to soils, another interesting opportunity of CE L approaches consists in the optimization of the different circuits available to valorize zootechnical waste, whose contribution to local air pollution, odors, greenhouse gas emissions, and nitrate contamination of soils and aquifers are known. In this regard, an innovative approach is suggested by a recent paper, consisting in the coupling of the HTC of swine manure with the AD of OFMSW to produce energy, compost, and hydrochar [142]. Both compost and hydrochar could be used locally for agricultural applications, thus closing the cycle of the organic waste in a rural context.…”
Section: Discussion and Future Challengesmentioning
confidence: 99%
“…In the perspective of reducing the carbon emissions, improving resource efficiency, minimizing waste production and potential damages to soils, another interesting opportunity of CE L approaches consists in the optimization of the different circuits available to valorize zootechnical waste, whose contribution to local air pollution, odors, greenhouse gas emissions, and nitrate contamination of soils and aquifers are known. In this regard, an innovative approach is suggested by a recent paper, consisting in the coupling of the HTC of swine manure with the AD of OFMSW to produce energy, compost, and hydrochar [142]. Both compost and hydrochar could be used locally for agricultural applications, thus closing the cycle of the organic waste in a rural context.…”
Section: Discussion and Future Challengesmentioning
confidence: 99%
“…Dahlin et al [57] compared the concentration of cadmium (Cd) in wheat grains from land fertilized with biofertilizer and land fertilized in a traditional manner and found that the inappropriate use of chlorine in soils with digested material significantly increased the concentration of Cd in the crop products. For Rada et al [58], food waste management at the local level has the risk of bad smell as a negative factor, but this can be minimized with AD and, if the organic volume is high, additional treatment plants will be needed, raising the cost of the infrastructure needed to build the digesters.…”
Section: Facilitators Description Referencesmentioning
confidence: 99%
“…High transportation costs when the biodigester is far away from the point of waste collection or from the land where the biofertilizer is to be used [35,36,54,58,62] Lack of knowledge about the energy potential of the sector Lack of awareness of the energy potential that can be obtained with the use of biogas [40] Population awareness Lack of knowledge of the population about the advantages of biodigesters and the need for proper separation of waste [40,58] Contamination of soil, air, water, etc.…”
Section: Difficulty To Perform and High Transportation Costsmentioning
confidence: 99%
“…Renewable energy is vital as an alternative source of energy. Due to the continuous rapid depletion of fossil fuels, renewable energy is gaining increasing popularity to supplement and, perhaps in the future, replace the role of fossil fuels [1]- [4]. In this context, an important point is the consideration of the national priorities.…”
Section: Introductionmentioning
confidence: 99%